Management Productive Waqf Optimalization (Case Study Tabung Wakaf Indonesia) - Lc., Izzuddin Edi Siswanto, MA; SEI., Hendro Wibowo, MM., RFP; SE, Edy Suprapto; SE, Isminidar (Universiti Sains Islam Malaysia, 2024)
Waqaf is an instrument which is offered by Islam religion embodying the moral aspect that emphasizes the value of social and economic justice. The history has recorded how the waqaf has managed to become a supporting community economic development in the Caliphate era. Waqaf possessed a great potential to bring fresh air to the development of the Indonesian economy supported by economists in scientific analysis and conventional as well as Ulama and Fiqih scholars. Therefore,the optimalization of the management of productive waqafis interesting to study in the form of scientific papers. The motivation of this study is starting by looking from the very slow development of waqaf in Indonesia. Meanwhile Indonesia has the world's largest waqaf potential. This is because of the lack of management of waqaf both in terms of accumulation and development of waqaf assets.The process of optimizing the management of productive waqaf is needed by adopting the theory of the application of Islamic economists and from other countries which have been further develop in productive waqaf. This research attempt to reveal anything regarding productive waqafwhich are not yet able to provide the optimal results. Afterwards, this current study also attempt to provide the alternative productive waqaf development, thus the Nazhir is expected to apply it in the field as an effort to improve the management of productive waqaf.